The rights of wives living with HIV/AIDS according to the perspective of Islamic family law - Abu Bakar, Md Zawawi (American-Eurasian Network for Scientific Information (AENSI Publisher), 2013)
The Islamic Family Laws (IFL) grants certain rights to each husband and wife including the ones living with HIV/AIDS.The infection rate of HIV/AIDS among housewives increases each year. The situation has raised several distressing issues; among them is the effectiveness of preventive measures that can be applied by the wives.Most of the women contracted the infectious disease through heterosexual relationship (with their infected husbands).The purpose of the research is to learn the extent of information a wife living with HIV/AIDS has on her right in the IFL. The qualitative research was conducted in the state of Kedah applying the interview technique (case study) as source of data collection.Eight individuals were interviewed to extract information and the data required.The results showed that the respondents were unaware of their rights in the IFL and thus, lack of knowledge to prevent the infection of HIV/AIDS from their respective husbands.Based on the research findings, several recommendations were drawn to lift the spirit of women living with HIV/AIDS and live in a normal life.